Elucidating the role of pH and total solids content in the co-production of biohydrogen and carboxylic acids from food waste via lactate-driven dark fermentation. (15th April 2023) - Regueira-Marcos, Lois; García-Depraect, Octavio; Muñoz, Raúl
Graphical abstract: Highlights: LD-DF is a feasible platform for co-producing H2 and MCCAs from Food Waste. Outstanding maximum volumetric H2 production rates of up to 13 NL/L-d were achieved. A pH of 6.5 and a TS of 7.5% supported to the highest H2 production performance. H2 production improved with low lactate buildup but ceased with lactate exhaustion. Abstract: Notwithstanding lactate-driven dark fermentation (LD-DF) can cope with inhibition issues associated with the over-proliferation of lactate producers, there is still a knowledge gap about the role of key operational parameters. In this study, the effect of pH and total solids (TS) content on the co-production of hydrogen and carboxylic acids, including medium-chain carboxylic acids (MCCAs), from food waste (FW) via LD-DF was investigated. A series of batch fermentations was conducted, first, without pH control, and then at fixed pH values of 5.5, 6.0 and 6.5, while maintaining constant the TS content at 5 %. It was observed that the higher the operational pH, the lower the accumulation of lactate and the higher the extent and rate of hydrogen production, sustaining a maximum hydrogen production yield and rate of 81 NmL/g VS fed and 9 NL/L-d, respectively, at pH 6.5. In a second series of batch tests, the TS content was adjusted to 5, 7.5 and 10 % while pH was set at 6.5. The highest hydrogen production performance (103 NmL/g-VS fed and 13.3 NL/L-d) was achieved at 7.5 % TS, which also resulted in the highest accumulation of MCCAs, particularly of caproate, with an associated titer of 8.7 g/L. Hydrogen production plateaued with the exhaustion of lactate regardless of the condition tested. Further assessment through biochemical methane potential tests showed that LD-DF effluents can be alternatively valorised into biogas. Overall, the results obtained confirmed the key role of pH and TS content in the LD-DF of FW and suggested that this non-conventional route may be an alternative approach to cope with lactate flux diverted toward undesirable non-hydrogen-producing metabolic pathways.